A strong association of human leukocyte antigen-associated Pol and Gag mutations with clinical parameters in HIV-1 subtype A/E infection. (13th March 2016) - Van Tran, Giang; Chikata, Takayuki; Carlson, Jonathan M.; Murakoshi, Hayato; Nguyen, Dung Hoai; Tamura, Yoshiko; Akahoshi, Tomohiro; Kuse, Nozomi; Sakai, Keiko; Sakai, Sachiko; Cobarrubias, Kyle; Oka, Shinichi; et al.
Abstract : Objectives: Identification of human leukocyte antigen-associated HIV-1 polymorphisms (HLA-APs) in different global populations furthers our understanding of HIV-1 pathogenesis and may help identify candidate immunogens for HIV vaccines targeted to these populations. Although numerous population-based studies identifying HLA-APs have been conducted in HIV-1 subtype B- and subtype C-infected cohorts, few have focused on subtype A/E. Design: We investigated HLA-APs in a cohort of chronically HIV-1 subtype A/E-infected Vietnamese individuals. Methods: HLA-APs in HIV-1 Gag, Pol, and Nef regions from 388 treatment-naive individuals chronically infected with HIV-1 subtype A/E were analyzed using phylogenetically informed approaches. Results: A total of 303 HLA-APs were identified. HLA-APs occurring at six positions in Gag and six positions in Pol were significantly associated with higher plasma viral load (pVL), whereas HLA-APs occurring at two positions in Gag and 13 positions in Pol were significantly associated with lower CD4 + T-cell counts. Furthermore, the proportion of Pol codons harboring an HLA-AP specific to the host's HLA correlated positively with HIV-1 pVL ( R  = 0.22; P  < 0.0001) and inversely with CD4 + T-cell counts ( R  = –0.32; P  < 0.0001). Similarly, the proportion of HLA-associated Gag codons harboring host-specific HLA-AP correlated inversely with CD4 + T-cell counts ( R  = –0.13; P  = 0.01). Conclusion: These significant associations between HIV-1 amino acids adapted to Vietnamese HLA alleles and higher pVL and lower CD4 + T-cell counts suggests that accumulation of cytotoxic T cells escape mutations may influence clinical outcomes in HIV-1 subtype A/E-infected Vietnamese individuals. Abstract : Supplemental Digital Content is available in the text